Liming and Choice of Rootstocks as Cultural Techniques for Vines in Acid Soils - Conradie, W. J. (South African Journal of Enology and Viticulture, 2017)
The effect of soil acidity on the performance of Chenin blanc vines grafted on 15 rootstock cultivars was determined in a pot experiment by liming a typically acid soil at pH (KCI) 4,1 (Control), to a pH of 5,0 (Treatment 1) and pH 6,0 (Treatment 2). On average the shoot masses of vines from Treatment 1 and Treatment 2 were respectively 27% and 870/o higher than those of the control. Root masses were increased by 11 O/o and 320/o respectively, indicating that the locally accepted norm of liming acid soils to a pH of 5,0 or to a point where exchangeable aluminium is decreased to less than 0,2 meq/100 g of soil, may be insufficient for most rootstocks. The beneficial effect of lime on the performance of vines could have been partly due to an improvement in the structure of the soil as indicated by lower mechanical resistances of the limed soils. The detrimental effect of soil acidity on the performance of vines could be reduced by the correct choice of rootstocks. The cultivars 140 Ruggeri, USVIT 8-7, 110 Richter, 99 Richter and USVIT 2-1 were best suited for use on acid soils while 101-14 Mgt, 44-53 Malegue, S04 , Rupestris du Lot and USVIT 3-6 proved less suitable for the acid soil used in this investigation.